2016
DOI: 10.1039/c6ta06430b
|View full text |Cite
|
Sign up to set email alerts
|

Pd2Sn [010] nanorods as a highly active and stable ethanol oxidation catalyst

Abstract: The development of highly active, low cost and stable electrocatalysts for direct alcohol fuel cells remains a critical challenge. While Pd2Sn has been reported as an excellent catalyst for the ethanol oxidation reaction (EOR), here we present DFT analysis results showing the (100) and (001) facets of orthorhombic Pd2Sn to be more favourable for the EOR than (010). Accordingly, using tri-n-octylphosphine, oleylamine (OLA) and methylamine hydrochloride as size and shape directing agents, we produced colloidal P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 54 publications
2
72
0
Order By: Relevance
“…The use of TOP played an important role in facilitating the formation of the cubic shape by capping their {100} facets via selective adsorption of P‐based groups derived from TOP (Figure d). Recently, Cabot and co‐workers demonstrated the synthesis of orthogonal Pd 2 Sn nanorods (space group: Pnma) with different aspect ratios in OAm containing hexadecylammonium chloride (HDA·HCl) or methylamine hydrochloride (MAHC) with TOP as a stabilizer and capping agent at 300 °C ( Figure ) . The authors found that Cl – ions derived from HDA·HCl or MAHC could selectively desorb TOP from the {010} facets on the two ends of a nanorod, leading to anisotropic growth (Figure a).…”
Section: Synthetic Approaches To Intermetallic Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of TOP played an important role in facilitating the formation of the cubic shape by capping their {100} facets via selective adsorption of P‐based groups derived from TOP (Figure d). Recently, Cabot and co‐workers demonstrated the synthesis of orthogonal Pd 2 Sn nanorods (space group: Pnma) with different aspect ratios in OAm containing hexadecylammonium chloride (HDA·HCl) or methylamine hydrochloride (MAHC) with TOP as a stabilizer and capping agent at 300 °C ( Figure ) . The authors found that Cl – ions derived from HDA·HCl or MAHC could selectively desorb TOP from the {010} facets on the two ends of a nanorod, leading to anisotropic growth (Figure a).…”
Section: Synthetic Approaches To Intermetallic Nanocrystalsmentioning
confidence: 99%
“…b–e) TEM images of the Pd 2 Sn nanoparticles and nanorods with different lengths and diameters achieved by varying the concentration of Cl – ions and TOP. b–e) Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Synthetic Approaches To Intermetallic Nanocrystalsmentioning
confidence: 99%
“…It reveals that the 336.7 eV binding energy of Pd/BC-2 matched with representational Pd 3d signal peak. [56] The Pd (0) has more comparative valence than Pd (II) state in the Pd/BC-2 on account of the cumulative strength ratio. [55] The binding energy of Pd (0) appears at 336.1 eV (Pd 3d 5/ 2 ) and 341.45 eV (Pd 3d 3/2 ), while these of Pd (II) state can be seen at 336.9 eV (3d 5/2 ) and 342.4 eV (3d 3/2 ).…”
Section: Structure and Morphologymentioning
confidence: 99%
“…[55] The binding energy of Pd (0) appears at 336.1 eV (Pd 3d 5/ 2 ) and 341.45 eV (Pd 3d 3/2 ), while these of Pd (II) state can be seen at 336.9 eV (3d 5/2 ) and 342.4 eV (3d 3/2 ). [56] The Pd (0) has more comparative valence than Pd (II) state in the Pd/BC-2 on account of the cumulative strength ratio. Compared to binding energy (188.0 eV) of the pure boron, the higher shift of the B 1s signal reveals that the sp 2 carbon lattice exists boron.…”
Section: Structure and Morphologymentioning
confidence: 99%
“…ZnO template-assisted electrodeposition optimal Pd/Co ratio,a nd hollow and porousstructure 2015 [138] PdCo coreduction synergistic effectfrom the uniques tructure and chemical composition:t hin carbon shelli nhibits particlea gglomeration and alloying with Co modification of the electronic structureo fP d 2017 [139] PdCu coreduction by NaBH 4 3D network, self-supporting, and electronic interactions 2015 [140] PdCu coreduction smaller size, more Pd active sites on the surface, and good synergistic effects 2016 [141] PdCu coreduction by CO ultrathin sheet structure, cleans urfacec lean feature, 3D structure,a nd synergistic effect 2017 [142] PdFe one-pot thermald ecompositiondownward shifted d-bandc enter,easily formed oxygen-containings pecies, and stabilizing effect from supports 2015 [143] PdGe coreduction balance between adsorption energies of CH 3 CO and OH on the catalystsurface and presence of vacanciesi nt he inactive sites 2015 [144] PdNi coreductionsynergistic effectofP dNi particles and rGO support2018 [145] Ni@PdNi electrodepositionand galvanic replacementr eaction bifunctional mechanism that alleviates surface CO poisoning 2018 [146] PdPb coreductionoptimal electronic and geometric effects,a nd stable chemical configuration2 017 [147] PdRu seed-mediated growth optimal Pd/Ru ratio and bifunctional mechanism 2015 [148] PdSn coreductioni nt he presenceo fs ize-and shape-directing agents exposureoffavorable facets 2016 [149] PtCo coreductioni nt he presenceo fs ize-and shape-directing agents presence of activet hreefold hollow sites on platinum-rich high-indexf acets 2016 [150] PtCo coreductionb ycontrolled thermal treatment promotion of partial oxidationo fe thanolover CÀCb ond cleavage Pt 3 Co with Pt skin 2017 [151] PtCu coreductiona td ifferent pH valuesmorphological tailoring 2016 [152] PtCu coreductionmonodispersion,s mall sizes (sub-5 nm), and polyhedral structures 2017 [153] PtIr coreductiondendriticstructures, surface state, and controlled electronic structure2016 [154] PtNi coreductionb yoleylamine synergistic electronic and facet effects2017 [155] PtPd coreductioni nt he presenceo fr GO optimal Pt/Pd ratio, synergistic effect, and ligand effect 2014 [156] PtPd coreductioni nt he presenceo fr GO dendriticstructure, synergistice ffect, and good dispersion of rGO 2014 [157] PtPd coreductioni nt he presenceo fg raphene optimal Pt/Pd ratio and morphology tuning 2014 [158] PtPd coreductionb yNaBH 4 electronic effectsand bifunctional mechanism 2014 …”
Section: Systems Synthetic Strategy Mechanism Responsible For High Eomentioning
confidence: 99%